Preparation method and application of MOF-derived Co3O4 / honeycomb ceramic monolithic catalyst
Co3O4 is etched by nitrate solution to form MOF-derived Co3O4/honeycomb ceramic catalyst, which solves the problems of poor catalyst performance and pollution in the preparation process, and achieves efficient methane catalytic oxidation reaction and environmentally friendly preparation process.
Patent Information
- Application Number
- CN202411410467.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-14
AI Technical Summary
The existing Co3O4 catalysts have poor performance in methane-catalyzed oxidation reactions, and the traditional etching strategy uses acid/alkali reagents to cause contamination, making the preparation process not simple and efficient.
Co3O4 is etched with nitrate solution, and the MOF-derived Co3O4/honeycomb ceramic monolithic catalyst is formed by reacting with 2-methylimidazole and cobalt nitrate in methanol, which promotes the activity of surface lattice oxygen and accelerates the oxygen species. Activation avoids the use of acid/base reagents.
It significantly improves the performance of methane catalytic oxidation reaction, and a simple and efficient preparation process, reduces the temperature requirement of the catalyst, and avoids pollution problems in traditional methods.
Smart Images

Figure HDA0005077840600000011 
Figure HDA0005077840600000012 
Figure HDA0005077840600000021
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a MOF-derived Co3O4 / honeycomb ceramic monolithic catalyst, belonging to the fields of catalytic technology and environmental protection. Background Art
[0002] The growing demand for energy has led to an increasing use of traditional fuels, which has led to an increase in the accumulation of greenhouse gases and various pollutants in the atmosphere year by year. Developing and utilizing clean energy is one of the important ways to solve energy shortages and alleviate environmental pressure. Natural gas is a fossil fuel that is superior to coal and oil because its main component, methane, produces more heat and releases less carbon dioxide than other hydrocarbon fuels. However, due to the stable chemical properties of methane molecules, the utilization of natural gas through conventional oxidation requires a higher reaction temperature, and this process is accompanied by the escape of some unoxidized methane. Methane has been proven to be the second largest greenhouse gas, contributing about 25% to global warming, and its global warming potential far exceeds that of carbon dioxide. Catalytic oxidation technology is recognized as one of the best strategies for controlling methane emissions. Under the action of a catalyst, the temperature required for complete oxidation of methane is significantly reduced.
[0003] The development of highly active catalysts is the key to catalytic oxidation technology. In the catalytic oxidation of methane, Pd-based catalysts have the best performance, but their high price limits their large-scale application. Therefore, designing high-performance non-precious metal catalysts is more in line with future trends. As a typical transition metal oxide, Co3O4 has the potential for practical application in a variety of catalytic reactions due to its good redox properties, high oxygen mobility, and easy generation of active oxygen species. MOF derivatization is a common method for synthesizing Co3O4. By heat treating MOF materials, a large number of unsaturated metal sites can be obtained, but the performance of the Co3O4 catalyst obtained by this method in the catalytic oxidation of methane is still poor. Therefore, there is an urgent need to develop a highly active Co3O4 catalyst for catalytic oxidation of methane. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a MOF-derived Co3O4 / honeycomb ceramic monolithic catalyst and its application in the catalytic oxidation of methane. By etching Co3O4 with a nitrate solution, the activity of surface lattice oxygen in Co3O4 is promoted and the activation of oxygen species is accelerated, thereby improving the performance in the catalytic oxidation reaction of methane. At the same time, the etching strategy of the present invention avoids the use of acid / base reagents in traditional etching strategies, making the preparation process more concise, efficient and environmentally friendly.
[0005] In order to achieve the above object, the technical solution of the present invention is as follows:
[0006] In one aspect, the present invention provides a method for preparing a MOF-derived Co3O4 / honeycomb ceramic monolithic catalyst, the method comprising the following steps:
[0007] (1) dissolving cobalt nitrate in methanol to obtain solution A, and dissolving 2-methylimidazole in methanol to obtain solution B;
[0008] (2) Add solution B dropwise into solution A and stir, then age in the dark for 20 to 40 hours;
[0009] (3) washing the precipitate with methanol and drying;
[0010] (4) dispersing the powder obtained in step (3) and the pretreated honeycomb ceramic in a nitrate solution, ultrasonically treating, washing to remove excess ions, drying, and then calcining in air to obtain a MOF-derived Co3O4 / honeycomb ceramic monolithic catalyst.
[0011] In the above technical solution, further, in step (1), the molar ratio of 2-methylimidazole to cobalt nitrate is 2:1 to 5:1.
[0012] In the above technical solution, further, in step (4), the nitrate is one of cobalt nitrate, zinc nitrate, manganese nitrate and nickel nitrate, and the concentration is 0.05-0.3 mol / L.
[0013] In the above technical solution, further, in step (4), the honeycomb ceramic is one of cordierite and alumina.
[0014] In the above technical solution, further, in step (4), the pretreatment method of the honeycomb ceramic is: soaking in acetic acid with a concentration of 0.1 to 0.5 mol / L for 6 to 12 hours.
[0015] In the above technical solution, further, in step (4), the ultrasonic conditions are: power 100-120W, ultrasonic time 1-2h.
[0016] In the above technical solution, further, in step (4), the calcination temperature is 400-500° C., the calcination time is 4-8 hours, and the heating rate is 1-5° C. / min.
[0017] Another aspect of the present invention provides a MOF-derived Co3O4 / honeycomb ceramic monolithic catalyst prepared by the above preparation method, wherein the catalyst has Co3O4 as an active component and honeycomb ceramic as a carrier.
[0018] The present invention also provides an application of the Co3O4 / honeycomb ceramic monolithic catalyst derived from the MOF in a methane catalytic oxidation reaction.
[0019] The beneficial effects of the present invention are:
[0020] (1) The present invention promotes the activity of surface lattice oxygen in Co3O4 and accelerates the activation of oxygen species by etching Co3O4 with a nitrate solution, thereby improving the performance in the catalytic oxidation reaction of methane.
[0021] (2) The etching strategy using nitrate solution proposed in the present invention avoids the pollution caused by traditional acid / base etchants, making the preparation process more concise, efficient and environmentally friendly, and has practical application potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The actual pictures of the Co3O4-0.1Co / cordierite monolithic catalyst and cordierite honeycomb ceramic prepared in Example 1, a is Co3O4-0.1Co / cordierite, b is cordierite honeycomb ceramic;
[0023] Figure 2 The CH4 conversion rate of the catalysts of Examples 1-6 and Comparative Examples 1-2 varies with temperature;
[0024] Figure 3 H2-TPR diagram of the catalysts of Examples 1-3 and Comparative Example 1;
[0025] Figure 4 It is the O2-TPD diagram of the catalyst of Examples 1-3 and Comparative Example 1. DETAILED DESCRIPTION
[0026] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and cannot be interpreted as limiting the present invention.
[0027] Unless otherwise specified, the materials used in the embodiments of the present invention can be obtained through commercial channels or prepared according to conventional methods well known to those skilled in the art.
[0028] Example 1
[0029] (1) Dissolve 29.1 g Co(NO3)2·6H2O and 32.8 g 2-methylimidazole in 250 mL methanol respectively;
[0030] (2) The above-mentioned Co(NO3)2·6H2O methanol solution and 2-methylimidazole methanol solution were mixed and stirred for 30 minutes, and then aged at room temperature in the dark for 24 hours;
[0031] (3) washing the obtained precipitate several times and drying it overnight to obtain a precursor powder;
[0032] (4) pre-treating the cordierite by immersing it in a 0.5 mol / L acetic acid solution for 6 h and then drying it, wherein the size of the cordierite is 11 mm in diameter, 25 mm in height, and 1×1 mm in pore size;
[0033] (5) The precursor powder and the pretreated cordierite were immersed in a 0.1 mol / L cobalt nitrate solution and ultrasonicated at 100 W for 90 min. After washing and drying, the temperature was raised to 400 °C at a rate of 1 °C / min in an air atmosphere and maintained for 4 h. The resulting monolithic catalyst was recorded as Co3O4-0.1Co / cordierite.
[0034] The actual objects of Co3O4-0.1Co / cordierite and cordierite carrier prepared in Example 1 are as follows: Figure 1 As shown, compared with cordierite, Co3O4-0.1Co / cordierite is black and the color distribution is uniform, which indicates that Co3O4 has been successfully coated on cordierite.
[0035] Example 2
[0036] (1) Dissolve 29.1 g Co(NO3)2·6H2O and 32.8 g 2-methylimidazole in 250 mL methanol respectively;
[0037] (2) The above-mentioned Co(NO3)2·6H2O methanol solution and 2-methylimidazole methanol solution were mixed and stirred for 30 min and then aged at room temperature in the dark for 24 h;
[0038] (3) washing the obtained precipitate several times and drying it overnight to obtain a precursor powder;
[0039] (4) pre-treating the cordierite by immersing it in a 0.5 mol / L acetic acid solution for 6 h and then drying it, wherein the size of the cordierite is 11 mm in diameter, 25 mm in height, and 1×1 mm in pore size;
[0040] (5) The precursor powder and cordierite were immersed in a 0.3 mol / L cobalt nitrate solution and ultrasonicated at 100 W for 90 min. After washing and drying, the temperature was raised to 400 °C at a rate of 1 °C / min in an air atmosphere and maintained for 4 h. The resulting monolithic catalyst was recorded as Co3O4-0.3Co / cordierite.
[0041] Example 3
[0042] (1) Dissolve 29.1 g Co(NO3)2·6H2O and 32.8 g 2-methylimidazole in 250 mL methanol respectively;
[0043] (2) The above-mentioned Co(NO3)2·6H2O methanol solution and 2-methylimidazole methanol solution were mixed and stirred for 30 min and then aged at room temperature in the dark for 24 h;
[0044] (3) washing the obtained precipitate several times and drying it overnight to obtain a precursor powder;
[0045] (4) pre-treating the cordierite by immersing it in a 0.5 mol / L acetic acid solution for 6 h and then drying it, wherein the size of the cordierite is 11 mm in diameter, 25 mm in height, and 1×1 mm in pore size;
[0046] (5) The precursor powder and cordierite were immersed in a 0.05 mol / L cobalt nitrate solution and ultrasonicated at 100 W for 90 min. After washing and drying, the temperature was raised to 400 °C at a rate of 1 °C / min in an air atmosphere and maintained for 4 h. The resulting monolithic catalyst was recorded as Co3O4-0.05Co / cordierite.
[0047] Example 4
[0048] (1) Dissolve 29.1 g Co(NO3)2·6H2O and 32.8 g 2-methylimidazole in 250 mL methanol respectively;
[0049] (2) The above-mentioned Co(NO3)2·6H2O methanol solution and 2-methylimidazole methanol solution were mixed and stirred for 30 minutes, and then aged at room temperature in the dark for 24 hours;
[0050] (3) washing the obtained precipitate several times and drying it overnight to obtain a precursor powder;
[0051] (4) Soaking cordierite in a 0.5 mol / L acetic acid solution for 6 h and then drying it, wherein the size of the cordierite is 11 mm in diameter, 25 mm in height, and 1×1 mm in pore size;
[0052] (5) The precursor powder and cordierite were soaked in a 0.1 mol / L nickel nitrate solution and ultrasonicated at 100 W for 90 min. After washing and drying, the temperature was raised to 400 °C at a rate of 1 °C / min in an air atmosphere and maintained for 4 h. The resulting monolithic catalyst was recorded as Co3O4-0.1Ni / cordierite.
[0053] Example 5
[0054] (1) Dissolve 29.1 g Co(NO3)2·6H2O and 32.8 g 2-methylimidazole in 250 mL methanol respectively;
[0055] (2) The above-mentioned Co(NO3)2·6H2O methanol solution and 2-methylimidazole methanol solution were mixed and stirred for 30 min and then aged at room temperature in the dark for 24 h;
[0056] (3) washing the obtained precipitate several times and drying it overnight to obtain a precursor powder;
[0057] (4) pre-treating the alumina ceramic by immersing it in a 0.5 mol / L acetic acid solution for 6 h and then drying it, wherein the size of the alumina ceramic is 11 mm in diameter, 25 mm in height, and 1×1 mm in pore size;
[0058] (5) The precursor powder and alumina ceramic were immersed in a 0.05 mol / L manganese nitrate solution and ultrasonicated at 100 W for 90 min. After washing and drying, the temperature was increased to 400 °C at a rate of 1 °C / min in an air atmosphere and maintained for 4 h. The obtained integrated catalyst was recorded as Co3O4-0.05Mn / alumina.
[0059] Example 6
[0060] (1) Dissolve 29.1 g Co(NO3)2·6H2O and 32.8 g 2-methylimidazole in 250 mL methanol respectively;
[0061] (2) The above-mentioned Co(NO3)2·6H2O methanol solution and 2-methylimidazole methanol solution were mixed and stirred for 30 min and then aged at room temperature in the dark for 24 h;
[0062] (3) washing the obtained precipitate several times and drying it overnight to obtain a precursor powder;
[0063] (4) pre-treating the alumina ceramic by immersing it in a 0.5 mol / L acetic acid solution for 6 h and then drying it, wherein the size of the alumina ceramic is 11 mm in diameter, 25 mm in height, and 1×1 mm in pore size;
[0064] (5) The precursor powder and alumina ceramic were immersed in a 0.05 mol / L zinc nitrate solution and ultrasonicated at 100 W for 90 min. After washing and drying, the temperature was raised to 400 °C at a rate of 1 °C / min in an air atmosphere and maintained for 4 h. The resulting integrated catalyst was recorded as Co3O4-0.05Zn / alumina.
[0065] Comparative Example 1
[0066] (1) Dissolve 29.1 g Co(NO3)2·6H2O and 32.8 g 2-methylimidazole in 250 mL methanol respectively;
[0067] (2) Soaking cordierite in a 0.5 mol / L acetic acid solution for 6 h and then drying it, wherein the size of the cordierite is 11 mm in diameter, 25 mm in height, and 1×1 mm in pore size;
[0068] (3) The above-mentioned Co(NO3)2·6H2O methanol solution and 2-methylimidazole methanol solution were mixed and the cordierite was placed therein and stirred for 30 min and then aged at room temperature in the dark for 24 h;
[0069] (4) The cordierite was taken out, washed and dried, and then heated to 400°C at a rate of 1°C / min in an air atmosphere and maintained for 4 hours. The obtained monolithic catalyst was recorded as Co3O4 / cordierite.
[0070] Comparative Example 2
[0071] (1) Dissolve 29.1 g Co(NO3)2·6H2O and 32.8 g 2-methylimidazole in 250 mL methanol respectively;
[0072] (2) The above-mentioned Co(NO3)2·6H2O methanol solution and 2-methylimidazole methanol solution were mixed and stirred for 30 min and then aged at room temperature in the dark for 24 h;
[0073] (3) washing the obtained precipitate several times and drying it overnight to obtain a precursor powder;
[0074] (4) Soaking cordierite in a 0.5 mol / L acetic acid solution for 6 h and then drying it, wherein the size of the cordierite is 11 mm in diameter, 25 mm in height, and 1×1 mm in pore size;
[0075] (5) The precursor powder and cordierite were immersed in a 0.6 mol / L cobalt nitrate solution and ultrasonicated at 100 W for 150 min. After washing and drying, the temperature was raised to 400 °C at a rate of 1 °C / min in an air atmosphere and maintained for 4 h. The resulting monolithic catalyst was recorded as Co3O4-0.6Co / cordierite.
[0076] Test Example 1
[0077] The catalysts prepared in Examples 1, 2, 3, 4, 5, 6 and Comparative Examples 1 and 2 were respectively loaded into a self-made quartz fixed bed reactor, and a mixed gas (1% CH4, 20% O2, 79% N2) was introduced to adjust the space velocity to 30,000 mL / (g Co3O4 h), the temperature was increased during the test to test its activity; the CH4 concentration in the tail gas of the fixed bed was detected at each temperature using a gas chromatograph equipped with a flame ionization detector (FID). Figure 2 It can be seen that the CH4 conversion rate of the monolithic catalysts prepared in Examples 1, 2, 3, 4, 5, 6 and Comparative Examples 1 and 2 increases with increasing temperature. The performance of the catalyst etched with a suitable concentration of nitrate solution is significantly improved, T 90 (Temperature when methane conversion rate is 90%) drops from 460°C to 365-380°C.
[0078] Using H2-TPR( Figure 3 ) and O2-TPD( Figure 4 ) characterization technology was used to explore the reasons for the improvement of catalyst performance. Figure 3 The two main reduction peaks are attributed to Co 3+ →Co 2+ and Co 2+ →Co 0 , the temperature corresponding to the reduction peak reflects the activity of the surface lattice oxygen species. It can be clearly seen that the etching of the Co3O4 precursor by the nitrate solution increases the activity of the lattice oxygen. In the O2-TPD test, the sample is first pretreated at high temperature to remove the surface lattice oxygen in the sample, followed by O2 treatment, and finally programmed temperature increase to compare the sample's ability to activate molecular oxygen by observing the desorption amount of oxygen species. Figure 4 It can be seen that the amount of surface lattice oxygen desorbed at 200-600°C in Examples 1, 2, and 3 is greater than that in Comparative Example 1, which indicates that the ability of activating molecular oxygen in Examples 1, 2, and 3 is significantly better than that in Comparative Example 1, and the surface lattice oxygen consumed during the oxidation reaction can be quickly replenished. In summary, the nitrate solution etching strategy in the present invention promotes the activity of surface lattice oxygen in Co3O4 and accelerates the activation of oxygen species, which is the reason why the MOF-derived Co3O4 / cordierite catalyst of the present invention has excellent performance.
[0079] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the implementation methods. The protection scope of the present invention shall be subject to the scope defined in the claims. Other different forms of changes or modifications may be made based on the above description. Obvious changes or modifications derived therefrom are still within the protection scope of the present invention.
Claims
1. A method for preparing a MOF-derived Co3O4 / honeycomb ceramic monolithic catalyst, characterized in that: The method comprises the following steps: (1) dissolving cobalt nitrate in methanol to obtain solution A, and dissolving 2-methylimidazole in methanol to obtain solution B; (2) Add solution B dropwise into solution A and stir, then age in the dark for 20 to 40 hours; (3) washing the precipitate with methanol and drying; (4) dispersing the powder obtained in step (3) and the pretreated honeycomb ceramic in a nitrate solution, ultrasonically treating, washing and drying, and then calcining in air to obtain a MOF-derived Co3O4 / honeycomb ceramic monolithic catalyst.
2. The preparation method according to claim 1, characterized in that: In step (1), the molar ratio of 2-methylimidazole to cobalt nitrate is 2:1 to 5:
1.
3. The preparation method according to claim 1, characterized in that: In step (4), the nitrate is one of cobalt nitrate, zinc nitrate, manganese nitrate and nickel nitrate, and the concentration is 0.05-0.3 mol / L.
4. The preparation method according to claim 1, characterized in that: In step (4), the honeycomb ceramic is one of cordierite and alumina.
5. The preparation method according to claim 1, characterized in that: In step (4), the pretreatment method of the honeycomb ceramic is: soaking in acetic acid with a concentration of 0.1 to 0.5 mol / L for 6 to 12 hours.
6. The preparation method according to claim 1, characterized in that: In step (4), the ultrasonic conditions are: power 100-120 W, and ultrasonic time 1-2 h.
7. The preparation method according to claim 1, characterized in that: In step (4), the calcination temperature is 400-500° C., the calcination time is 4-8 hours, and the heating rate is 1-5° C. / min.
8. A MOF-derived Co3O4 / honeycomb ceramic monolithic catalyst prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The catalyst uses Co3O4 as an active component and honeycomb ceramics as a carrier.
9. Use of the Co3O4 / honeycomb ceramic monolithic catalyst derived from MOF according to claim 8 in the catalytic oxidation reaction of methane.